Implementasi Pendidikan Agama Kristen dalam Masyarakat Majemuk - Wiranto Wiranto; Harun Puling; Susiana Lase; Semuel L. Topayung (Damai : Jurnal Pendidikan Agama Kristen dan Filsafat, 2024)
Religious beliefs and culture cannot be separated from one another because religion exists within a particular culture, and local culture influences religion. Although religion is supposed to encourage humanity to create peace and prosperity on Earth, it has instead become one of the factors causing violence and the destruction of humanity, necessitating actions to prevent these issues from arising. Christian Religious Education (PAK) has an educational, social, and participatory role in the life of a pluralistic society. Essentially, PAK is an effective learning medium to instill Christian principles in every member of the church, serving as a foundation for their existence in society. The method used in the writing of this paper is a descriptive qualitative method.